2000
DOI: 10.1002/(sici)1098-2736(200001)37:1<44::aid-tea4>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Linking Brain Growth with the Development of Scientific Reasoning Ability and Conceptual Change during Adolescence

Abstract: The hypothesis that an early adolescent brain growth plateau and spurt exists and that this plateau and spurt influence students' ability to reason scientifically and to learn theoretical science concepts was tested. In theory, maturation of the prefrontal lobes during early adolescence allows for improvements in students' abilities to inhibit task-irrelevant information and coordinate task-relevant information, which along with both physical and social experience influences scientific reasoning ability and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 49 publications
6
56
1
5
Order By: Relevance
“…It appears that inhibition can explain from 18 (Thibault, 2013) to 29 percent (Kwon & Lawson, 2000) of the conceptual gain in certain tests, including the well-known Force Concept Inventory (Hestenes, Wells, & Swackhammer, 1992), in a semester.…”
Section: Other Researchsupporting
confidence: 92%
“…It appears that inhibition can explain from 18 (Thibault, 2013) to 29 percent (Kwon & Lawson, 2000) of the conceptual gain in certain tests, including the well-known Force Concept Inventory (Hestenes, Wells, & Swackhammer, 1992), in a semester.…”
Section: Other Researchsupporting
confidence: 92%
“…We further focused on middle-school students because prior research has documented relationships between the measures relevant to our research questions in this age group. There is a correlation between scientific reasoning and WCST, a measure of complex cognitive ability, in middle-and high-school students (Kwon & Lawson, 2000). In addition, prior research has found a relation between achievement in mathematics, a subject closely related to science, and motivational orientation -possessing an incremental versus entity theory of implicit intelligence -in middle-school students (Blackwell, Trzesniewski, & Dweck, 2007).…”
Section: Introductionmentioning
confidence: 82%
“…That better scientific reasoning was associated with making more perseverative errors on the WCST was surprising given that such errors are associated with lesions to prefrontal cortex (Milner, 1963), with lower executive function and psychometric intelligence (Miyake et al, 2000), and with worse logico-scientific reasoning in middle and high school children (Kwon & Lawson, 2000). We offered a post hoc interpretation of this finding above, which we articulate further here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations